The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3390/sports9090128
|View full text |Cite
|
Sign up to set email alerts
|

Enjoyment of Physical Activity—Not MVPA during Physical Education—Predicts Future MVPA Participation and Sport Self-Concept

Abstract: There exists a general understanding that physical education (PE) is a means to create a physically healthy population. However, disagreements arise over primary practices within PE to achieve this end. The primary divergence is whether PE facilitators should primarily ensure participants exert a specific level of energy during class or develop their confidence, competence, knowledge, and motivation for meaningful physical activity (PA) participation outside of the PE classroom (referred to as physical literac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…In the literature, an important factor predicting moderate-vigorous physical activity (MVPA) was the gender variable. It is understood that MVPA-related boys have a predominantly higher MVPA than girls (Gouveia et al, 2021;Laiño et al, 2019;Lee, 2019;Ramer et al, 2021;Wang and Zhou, 2022;Woodfield et al, 2022). In the study of To et al, (2018), while the MVPA percentage of boys was found to be higher than that of girls during school days, no significant difference was observed in the MVPA value according to the gender on holidays.…”
Section: Physical Activity and Gendermentioning
confidence: 88%
See 1 more Smart Citation
“…In the literature, an important factor predicting moderate-vigorous physical activity (MVPA) was the gender variable. It is understood that MVPA-related boys have a predominantly higher MVPA than girls (Gouveia et al, 2021;Laiño et al, 2019;Lee, 2019;Ramer et al, 2021;Wang and Zhou, 2022;Woodfield et al, 2022). In the study of To et al, (2018), while the MVPA percentage of boys was found to be higher than that of girls during school days, no significant difference was observed in the MVPA value according to the gender on holidays.…”
Section: Physical Activity and Gendermentioning
confidence: 88%
“…Most countries aim to increase the level of physical activity by making primary school physical education compulsory. For example, the United States (Ramer et al, 2021), Australia (Dudley et al, 2012), Belgium (Iserbyt et al, 2022), China Hong Kong (Chow et al, 2008), Shanghai, China (Zhou et al, 2022), Korea (Lee, 2019), Maldives (Abdulla et al, 2022), Mexico (Hall-López et al, 2019), Turkey (Temel and Kangalgil, 2021) and Vietnam , countries such as act according to this goal.…”
Section: Introductionmentioning
confidence: 99%
“…The participants identified the importance of authentic relationships with students, this could foster a working alliance through the development of tripartite agency ( 34 ) leading to positive valuation of the PE classes ( 37 ). Children have identified that being engaged in a competency progression (i.e., learning something new) is fun ( 42 ) and upon reflection these children would associate enjoyment with the class leading to increased likelihood of lifelong participation in movement ( 14 , 43 ). Through the intentional construction of positive challenges using physical literacy in PE, participants also suggested this supported student engagement, motivation, and continued participation within their PE classes.…”
Section: Discussionmentioning
confidence: 99%
“…The SSG is proposed as a resource associated with a high level of enjoyment, with the potential to be applied in different contexts, such as school, sports, or health promotion programs [ 14 , 38 ]. In addition, the enjoyment of physical activity is considered key in the promotion of active lifestyles [ 6 , 39 ]. The results of this study showed that perceived enjoyment of both SSG regimens had a large inverse relationship with anthropometric variables but not to physical fitness or maturity status.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, schools’ physical education (PE) classes could offer a great opportunity to favor the development of physical fitness and motor skills in children and adolescents [ 4 ], encouraging them not only to comply with PA recommendations, [ 5 ] but also providing children and adolescents with tools with which they can continue with sports activities outside of a school context [ 6 ]. Unfortunately, it has been found that PE is not able to provide students with the motivation to create habits of practicing sports or other physical activities outside school hours [ 7 ].…”
Section: Introductionmentioning
confidence: 99%